2018
DOI: 10.1002/jts5.38
|View full text |Cite
|
Sign up to set email alerts
|

A self-regulatory approach to rational decisions: The implemental mindset optimizes economic decision making in situations requiring belief updating

Abstract: We examined the effects of the deliberative and implemental mindset on decision behavior when decisions require Bayesian updating of beliefs. In the decision task, in some situations Bayes' rule conflicts with a simple reinforcement‐based heuristic. Previous research showed that in these situations individuals rely on the faulty heuristic, hence committing many decision errors. We investigated deliberative and implemental mindset effects on the reinforcement heuristic. Results showed that the implemental minds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
(174 reference statements)
1
9
0
Order By: Relevance
“…Importantly, while deliberating, an individual is contemplating the pros and cons of an option, and is more receptive to all kinds of information; in the implemental state they become goal-oriented and become less attentive to new information (see Gollwitzer, 2012 ; Achtziger and Gollwitzer, 2018 for overview). Recent studies in this area of research have found that individuals who are manipulated into a deliberative mindset were slower in their decision making in a gamble ( Ludwig et al, 2020 ), while those in an implemental mindset were better suited to learning during a reinforcement learning task ( Li et al, 2019 ). No prior research in mindset theory has specifically tested sunk cost sensitivity, but it is possible that these states may also inform decisions to quit after re-evaluating less valuable options.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, while deliberating, an individual is contemplating the pros and cons of an option, and is more receptive to all kinds of information; in the implemental state they become goal-oriented and become less attentive to new information (see Gollwitzer, 2012 ; Achtziger and Gollwitzer, 2018 for overview). Recent studies in this area of research have found that individuals who are manipulated into a deliberative mindset were slower in their decision making in a gamble ( Ludwig et al, 2020 ), while those in an implemental mindset were better suited to learning during a reinforcement learning task ( Li et al, 2019 ). No prior research in mindset theory has specifically tested sunk cost sensitivity, but it is possible that these states may also inform decisions to quit after re-evaluating less valuable options.…”
Section: Introductionmentioning
confidence: 99%
“…We refrained from inducing a neutral mindset in which participants work on a simple, generic task prior to the measurement of dependent variables (e.g., report on everyday activities; Harmon‐Jones & Harmon‐Jones, ; Li et al, ). The purpose of a neutral mindset is to control for the potentially confounding impact of the increased workload prior to the measurement of the dependent variables and to account for the time that it takes to induce the mindsets before participants proceed to the main task.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the neutral mindset was included in a recent study as a control condition in addition to a baseline measurement to test potential effects of the neutral mindset on economic decision making. It was discovered that the neutral mindset condition and the baseline did not differ in terms of performance in the decision task (see Li et al, ). These previous studies demonstrated that mindset effects on several dependent measures were qualitatively different from a neutral mindset and a baseline measurement.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations